Androgenetic alopecia: evaluation of hormonal profile and its systemic implications - Pathak, Prateek; Adil, Mohammad; Sarshar, Fariz; Singh, Jyoti (International Journal of Research in Dermatology, 2023)
Background: Androgenetic Alopecia is a hereditary androgen-dependent disorder characterized by a gradual conversion of terminal hair into miniaturized hair with typical bitemporal recession and balding vertex and is considered the most common type of baldness characterized by progressive hair loss. This study evaluated the hormonal profile in males with androgenetic alopecia. This study evaluated the hormonal profile of early androgenetic alopecia in males. Methods: This prospective study included 84 patients attending the outpatient Department of Dermatology. Forty-four cases and 40 controls were included in the study. The study had 44 male patients presenting with complaints of grade ≥ 3 androgenetic alopecia in the age group 19-35 years, whereas 40 age and sex-matched patients attending Dermatology OPD for unrelated complaints with no history of hair loss or clinical examination suggestive of androgenetic alopecia were included in the control group. After a detailed history, and examination, testosterone, LH, FSH, Prolactin, and SHBG were estimated. Results: The mean age of onset was found to be 24.29±3.28 years. Positive family history was seen in 65.90% of patients. The mean testosterone, LH, FSH, prolactin, SHBG and free androgen index in cases versus controls was 6.44±2.58 versus 3.32±1.53 ng/ml, 8.01±2.64 IU/l versus 3.01±1.16 IU/l, 3.82±1.33 IU/l versus 5.07±1.27 IU/l, 15.50±5.11 ng/ml versus 9.84±3.91 ng/ml, 12.72±2.63 nmol/l versus 29.18±4.90 nmol/l and 51.03±21.78 versus 11.40±4.66 respectively. LH/FSH ratio was 2.17±0.54 versus 0.63±0.27. These parameters had p values <0.05 and were statistically significant. Conclusions: Our study concluded that serum testosterone, prolactin, LH, LH/FSH, and FAI are increased whereas serum FSH and SHBG are decreased in cases of androgenetic alopecia compared to controls.